The Implementation of CSR and GCG in Improving Financial Performance - Ariesa, Yeni; Fernando, Johnny; Melvira , Melvira; Putra Lie, Frandika; Sembiring, Lusiana (Technium Sustainability, 2021)
The aim of this research is to examine the implementation of CSR and GCG in improving financial performance in the consumer goods industry sector in 2015-2019. The research method approach uses deductive, quantitative types and descriptive properties. The number of consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) are 53 companies and the sample that meets the criteria according to purposive sampling is 12 companies. Data analysis used SEM with PLS approach model. PLS analysis was carried out with SmartPLS 3.0 software. The conclusion from the results indicate (CSR) has a negative effect while (GCG) shows a positive direction and have a significant impact on (ROE). The magnitude of this factor is 14%, through the adjusted R2 value, while the 86% could be explained as from other unexamined variables.